Formulasi dan Karakterisasi Transfersom Andrografolid - Syafanisa Alifia Rahma; Aulia Fikri Hidayat; Fitrianti Darusman (UNISBA Press, 2022)
Abstract. Andrographolide is the main bioactive compound in the sambiloto plant (Andrographis paniculata (Burm. f) Nees). Andrographolide is known to have poor solubility and low oral bioavailability. The transdermal route can be an alternative for the delivery of andrographolide compounds. Transfersome is one of the drug delivery systems that can increase the penetration ability of active substances in the transdermal route. This study aims to obtain the best andrographolide transfersome formula based on the characterization carried out and compare the penetration ability of the andrographolide transfersome and pure andrographolide. Four andrographolide transfersome formulas are made with variations in the ratio of phospholipid and surfactant concentrations, namely F1 (90:10), F2 (80:20), F3 (70:30), and F4 (60:40). Thin-layer hydration method was applied for transfersome preparation. The transfersomes obtained are characterized by the determination of entrapment efficiency, particle size, polydispersity index, and zeta potential. F4 with an entrapment efficiency value of 90.762%±0.592, particle size of 626,633±19,858 nm, polydispersity index of 0,456±0,055, and zeta potential of -4,067±1,097 mV was selected as the best andrographolide transfersome formula. In vitro penetration test was performed on the best transfersome andrographolide formula using the Franz diffusion cell method. The results of in vitro penetration tests show that andrographolide transfersome have better penetration ability than pure andrographolide. Andrographolide transfersome provide a cumulative amount andrographolide penetrated 108.583±0.918 μg/cm2 and flux 36.194±0.014 μg/cm2.h-1, while pure andrographolide provide a cumulative amount andrographolide penetrated 66,930±1,345 μg/cm2 and flux 22,301±0.448 μg/cm2.h-1. Abstrak. Andrografolid merupakan senyawa bioaktif utama yang terkandung dalam tanaman sambiloto (Andrographis paniculata (Burm. f) Nees). Andrografolid diketahui memiliki sifat kelarutan buruk dan bioavailabilitas oral rendah sehingga rute transdermal dapat menjadi alternatif untuk penghantaran senyawa andrografolid. Transfersom merupakan salah satu sistem penghantaran yang dapat meningkatkan kemampuan penetrasi zat aktif pada penghantaran dengan rute transdermal. Penelitian ini bertujuan untuk memperoleh formula transfersom andrografolid terbaik berdasarkan karakterisasi yang dilakukan dan membandingkan kemampuan penetrasi dari transfersom andrografolid dan andrografolid murni. Empat formula transfersom andrografolid dibuat dengan variasi perbandingan konsentrasi fosfolipid dan surfaktan yaitu F1 (90:10), F2 (80:20), F3 (70:30), dan F4 (60:40) menggunakan metode hidrasi lapis tipis. Transfersom yang diperoleh dikarakterisasi meliputi penentuan nilai persentase efisiensi penjerapan, ukuran partikel, indeks polidispersitas, dan potensial zeta. F4 dengan nilai efisiensi penjerapan 90,762%±0,592, ukuran partikel 626,633±19,858 nm, indeks polidispersitas 0,456±0,055, dan potensial zeta -4,067±1,097 mV dipilih sebagai formula transfersom andrografolid terbaik. Terhadap formula transfersom andrografolid terbaik dilakukan uji penetrasi in vitro dengan metode sel difusi Franz. Hasil uji penetrasi in vitro menunjukan bahwa transfersom andrografolid memiliki kemampuan penetrasi yang lebih baik dibandingkan andrografolid murni. Transfersom andrografolid memberikan nilai jumlah kumulatif terpenetrasi 108,583±0,918 µg/cm2 dan fluks 36,194±0,014 µg/cm2.jam-1. Sedangkan andrografolid murni memberikan nilai jumlah kumulatif terpenetrasi 66,930±1,345 µg/cm2 dan fluks 22,301±0,448 µg/cm2.jam-1.